2021
DOI: 10.3390/toxics9120348
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Induced Neurotoxicity through Impairment of Cross-Talk Pathways in Human Neuroblastoma Cell Line SH-SY5Y Differentiated with Retinoic Acid

Abstract: Manganese (Mn) is an important element; yet acute and/or chronic exposure to this metal has been linked to neurotoxicity and neurodegenerative illnesses such as Parkinson’s disease and others via an unknown mechanism. To better understand it, we exposed a human neuroblastoma cell model (SH-SY5Y) to two Mn chemical species, MnCl2 and Citrate of Mn(II) (0–2000 µM), followed by a cell viability assay, transcriptomics, and bioinformatics. Even though these cells have been chemically and genetically modified, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In recent years, the levels of fungicide residues in the environment have been on the rise. DFZ has been found to be highly stable, difficult to degrade, and easily transferable due to its physicochemical properties [31], allowing it to persist in aquatic systems, soil, and plants [32]. DFZ residues in food and the environment can be absorbed by the human body [33], posing a potential risk to human health.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the levels of fungicide residues in the environment have been on the rise. DFZ has been found to be highly stable, difficult to degrade, and easily transferable due to its physicochemical properties [31], allowing it to persist in aquatic systems, soil, and plants [32]. DFZ residues in food and the environment can be absorbed by the human body [33], posing a potential risk to human health.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Kazimierska et al [ 56 ] detected an excessive amount of manganese in insect-based dog foods. Although chronic manganese exposure has not been specifically studied in companion animals, it has been reported that it could be associated with neurotoxicity and neurodegenerative diseases [ 108 ]. Allergenic potential of insects has been described in individuals allergic to crustaceans, who can develop cross-allergic reactions when consuming insects, mainly due to the presence of arginine, chitinase, tropomyosin [ 109 ] and chitin in the insect exoskeleton [ 110 ].…”
Section: Current Use Of Insects As Food Ingredients For Dogs Cats And...mentioning
confidence: 99%
“…Manganese is a well-known neurotoxic element, but the mechanisms of this toxicity are still poorly understood. Hernández et al used SH-SY5Y neuroblastoma cells differentiated with retinoic acid to compare the toxicity of manganese chloride and manganese citrate [ 10 ]. Both chemical species of manganese induced similar toxicity governed by the disruption of protein metabolism, but with some differences.…”
mentioning
confidence: 99%